2017
DOI: 10.3390/ijerph14121456
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Phthalate Concentrations in Mothers and Their Children in Ireland: Results of the DEMOCOPHES Human Biomonitoring Study

Abstract: Background: Phthalates are chemicals which are widespread in the environment. Although the impacts on health of such exposure are unclear, there is evidence of a possible impact on the incidence of a diverse range of diseases. Monitoring of human exposure to phthalates is therefore important. This study aimed to determine the extent of phthalate exposure among mothers and their children in both rural and urban areas in Ireland, and to identify factors associated with elevated concentrations. It formed part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 29 publications
(60 reference statements)
5
16
2
Order By: Relevance
“…Data on urinary concentrations of phthalates in newborns are controversial. While some authors reported similar levels to those in the mothers [51], others observed two-or three times lower concentrations in offspring [52]. As for children, higher levels of urinary phthalates compared to adults have been found [53].…”
Section: Endocrine Disruptors In Dietmentioning
confidence: 98%
“…Data on urinary concentrations of phthalates in newborns are controversial. While some authors reported similar levels to those in the mothers [51], others observed two-or three times lower concentrations in offspring [52]. As for children, higher levels of urinary phthalates compared to adults have been found [53].…”
Section: Endocrine Disruptors In Dietmentioning
confidence: 98%
“…Certain phthalate metabolites (MEOHP, MEHHP, and MnBP) were lower in our study population, compared to previous European maternal studies. Our geometric mean for MEOHP was 2.59 µg/g creatinine, much lower than Czech Republic (11.68 µg/g creatinine), Slovakia (11.54 µg/g creatinine), Hungary (10.37 µg/g creatinine) [ 31 ], and Ireland (8.8 µg/g creatinine) [ 32 ]. Our participants geometric mean for MEHHP was 1.48 µg/g creatinine, lower compared to Czech Republic (18.45 µg/g creatinine), Slovakia (18.20 µg/g creatinine), Hungary (15.54 µg/g creatinine) [ 31 ], and Ireland (17.0 µg/g creatinine) [ 32 ].…”
Section: Discussionmentioning
confidence: 95%
“…Our geometric mean for MEOHP was 2.59 µg/g creatinine, much lower than Czech Republic (11.68 µg/g creatinine), Slovakia (11.54 µg/g creatinine), Hungary (10.37 µg/g creatinine) [ 31 ], and Ireland (8.8 µg/g creatinine) [ 32 ]. Our participants geometric mean for MEHHP was 1.48 µg/g creatinine, lower compared to Czech Republic (18.45 µg/g creatinine), Slovakia (18.20 µg/g creatinine), Hungary (15.54 µg/g creatinine) [ 31 ], and Ireland (17.0 µg/g creatinine) [ 32 ]. MnBP was not reported in Cerna et al, 2015 [ 31 ] for comparison, but was included in Cullen et al, 2017 [ 32 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations